Activity based chemical proteomics: profiling proteases as drug targets. - Heal,WP; Wickramasinghe,SR; Tate,EW (Curr Drug Discov Technol, 2008)
The pivotal role of proteases in many diseases has generated considerable interest in their basic biology, and in the potential to target them for chemotherapy. Although fundamental to the initiation and progression of diseases such as cancer, diabetes, arthritis and malaria, in many cases their precise role remains unknown. Activity-based chemical proteomics-an emerging field involving a combination of organic synthesis, biochemistry, cell biology, biophysics and bioinformatics-allows the detection, visualisation and activity quantification of whole families or selected sub-sets of proteases based upon their substrate specificity. This approach can be applied for drug target/lead identification and validation, the fundamentals of drug discovery. The activity-based probes discussed in this review contain three key features; a 'warhead' (binds irreversibly but selectively to the active site), a 'tag' (allowing enzyme 'handling', with a combination of fluorescent, affinity and/or radio labels), and a linker region between warhead and tag. From the design and synthesis of the linker arise some of the latest developments discussed here; not only can the physical properties (e.g., solubility, localisation) of the probe be tuned, but the inclusion of a cleavable moiety allows selective removal of tagged enzyme from affinity beads etc. The design and synthesis of recently reported probes is discussed, including modular assembly of highly versatile probes via solid phase synthesis. Recent applications of activity-based protein profiling to specific proteases (serine, threonine, cysteine and metalloproteases) are reviewed as are demonstrations of their use in the study of disease function in cancer and malaria.